Empowerment or Threat: Perceptions of Childhood Sexual Abuse in the #MeToo Era - de Roos, Melissa S. (Journal of interpersonal violence, 2022)
The rise of the #MeToo movement has shed light on the prominence of sexual violence, and its victims who often remain silent. Despite increasing awareness, victims or survivors of sexual violence who disclose may be faced with negative reactions such as disbelief or blame. Such reactions extend to child victims of sexual abuse. This study aimed to shed light on gender differences in responses to sexual violence against a backdrop of #MeToo. Through an online survey (N?=?253) on Amazon?s Mechanical Turk, we assessed participants? exposure to and perception of the #MeToo movement. In addition, we measured proximity to a victim or perpetrator of sexual violence. The effect of these variables on participants? response to a disclosure of childhood sexual abuse was examined. Results indicated that men are more likely to perceive the movement as threatening than women. Furthermore, a discrepancy in proximity to sexual violence emerged, with women more likely to know a victim and men more likely to know a perpetrator. In response to a disclosure of childhood sexual abuse, men were more likely to respond in a skeptical manner than women. Positive perceptions of the #MeToo movement translated into more supportive responses to a disclosure. Proximity to a victim of sexual violence did not impact how people responded to a disclosure, but proximity to a perpetrator was associated with a more negative response. Although the aim of this movement is to give a voice to victims of sexual violence, it may trigger a defensive response from men, which makes them more skeptical toward disclosures of victimization.